Periodontal Plastic Microsurgery in the Treatment of Deep Gingival Recession after Orthodontic Movement - Sérgio Kahn; Walmir Júnio de Pinho Reis Rodrigues; Marcos de Oliveira Barceleiro (Hindawi Limited, 2013)
Gingival recession is a condition that affects a large portion of the young and adult population and negatively affects the aesthetic aspects of the smile. Many factors are related to its development, including orthodontic movement beyond the osseous limits. Many treatment options have been proposed to cover the exposed root surface. The aim of this article was to describe three cases where a subepithelial connective tissue graft was performed, using a microsurgical technique, in the treatment of deep gingival recession after orthodontic treatment. This technique resulted in successful root coverage and keratinized tissue gain, improving the gingival esthetic pattern.